KEFASIHAN BACAAN AL-FATIHAH: ANALISIS DALAM KALANGAN PELAJAR KEJURUTERAAN - Siti Fatihah binti Ghazali; Ahmad Muhaimin bin Mohamad; Rohana binti Hamzah; Anita binti Abdul Rani; Rashidi bin Abbas; Mohd Suhardi bin Mat Jusoh (Journal of Islamic, Social, Economics and Development, 2022)
The aim of this research is to identify Al-Fatihah recitation level and SOLAT obligation among diploma, degree, and dual-degree students in engineering-based programme. Data collection was made by assigning individual task of university compulsory subject called Soft Skills. 712 Muslim students were involved in this research among 1165 registered students. All task and evaluation process via e-learning portal. Qualitative approach namely content analysis followed by quantitative method namely descriptive analysis, one-way ANOVA, and Pearson correlation test were used to answer research question and hypothesis testing. As a result, there are significant different of Al-Fatihah recitation level and SOLAT obligation among group. The correlation test show that there is significant correlation among the variable. The discussion assumes that cognitive and thinking level, personal and family background are the vital factors of analysis output. As a research contribution, the implication and further research was stated at the end of paper.